PERBANDINGAN PEMERIKSAAN TINJA METODE SEDIMENTASI DENGAN METODE NATIF DALAM MENDETEKSI SOIL TRANSMITTED HELMINTH - Nurhidayanti Nurhidayanti; Obie Permana (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Soil Transmitted Helminth (STH) is the most common intestinal parasific infection and in one of the contributors to the global disease burden. Diagnosis of Soil Transmitted Helminth desease can be done using sedimentation method and natif method. This study aims to find out the differences in sedimentation methods and natif methods in deteting Soil Transmitted Helminth Type of research conducted ind true experimental form. This research was conducted on March 27-29, 2021 at the Microbiology Laboratory of Muhammadiyah Institute of Health and Technology Palembang which numbered 35 respondents. The results obtained in this study were as many as 2 positive samples and 33 negative samples. In sample 1 there are 2 types of eggs Soil Transmitted Helminth namely eggs Ascaris lumbricoides and Trichuris trichiura on sedimentation method and natif method, while in sample 5 there are eggs Ascaris lumbricoides only on the natif method. The results of the research data were conduted using an alternative test Wilcoxon with a value of P = 0.317 means there is no difference that signifikan.the conclusion of this study was obtained by the examination that there is no difference in sedimentation with natiif method.